1994
DOI: 10.1007/bf00343949
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization and neuropeptide distributions in the equine enteric nervous system: an immunohistochemical study using whole-mount preparations from the small intestine

Abstract: The architecture and neurochemistry of the enteric nervous system was studied by use of whole-mount preparations obtained by microdissection of the horse jejunum. A myenteric plexus and two plexuses within the submucosa were identified. The external submucosal plexus lying in the outermost region of the submucosa had both neural and vascular connections with the inner submucosal plexus situated closer to the mucosa. Counts of neurones stained for NADH-diaphorase demonstrated the wide variation in size, shape a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
6
34
1
Order By: Relevance
“…While it is generally accepted that the boundary between ESP and ISP is the vascular arcades (Scheuermann et al 1987 a, b ;Brehmer et al 1994 ;Pearson, 1994 ;Balemba et al 1998), other authors have reported a third intermediate plexus in the submucous layer of the colon of the pig (Gunn, 1968), opposum (Christensen & Rick, 1987) and man (Hoyle & Burnstock, 1989). It is therefore not yet clear whether the ESP and ISP should be considered as 2 different plexuses.…”
Section: mentioning
confidence: 99%
See 4 more Smart Citations
“…While it is generally accepted that the boundary between ESP and ISP is the vascular arcades (Scheuermann et al 1987 a, b ;Brehmer et al 1994 ;Pearson, 1994 ;Balemba et al 1998), other authors have reported a third intermediate plexus in the submucous layer of the colon of the pig (Gunn, 1968), opposum (Christensen & Rick, 1987) and man (Hoyle & Burnstock, 1989). It is therefore not yet clear whether the ESP and ISP should be considered as 2 different plexuses.…”
Section: mentioning
confidence: 99%
“…However, in recent years it has been established that the submucous plexus comprises 2 different ganglionated plexuses, the internal submucous plexus (ISP) and the external submucous plexus (ESP) (Scheuermann et al 1987 b ;Messenger & Furness, 1990 ;Timmermans et al 1992 ;Pearson, 1994 ;Balemba et al 1998). The ISP is located adjacent to the mucosa and is proposed to be primarily Correspondence to Dr Vet.…”
Section: mentioning
confidence: 99%
See 3 more Smart Citations